Regionalism: old and new, theory and practice - Burfisher, Mary E.; Robinson, Sherman; Thierfelder, Karen (International Food Policy Research Institute, 2004)
The world economy after World War II has become much more integrated. Eight successive rounds of negotiations under the General Agreement on Tariffs and Trade (GATT) have resulted in significant global trade liberalization and there has been an accelerating trend toward regional integration in every part of the world. Most of the early attempts at regional trade agreements (RTAs) in the 1950 s and 1960 s, many of them among developing countries, met with little success.5 This first wave of regionalism has been eclipsed by the exponential growth in the number of RTAs formed over the past 10 years (figure 1). As of May 2003, 184 RTAs were in force. Almost every WTO member has now joined at least one RTA and some have entered 20 or more.